210 Intra-Operative Electrocorticography (ECoG) for Lesional Epilepsy: A Randomized Controlled Trial (IO-ECoG Trial). (April 2023) - Rajeev, Sreenath; Chandy Vilanilam, George; Abraham, Mathew; Easwer, Hariharan Venkat; Menon, Ramshekhar; Radhakrishnan, Ashalatha; Cherian, Ajith; Thomas, Sanjeev; Vimala, Smita; A N, Deepti
Abstract : INTRODUCTION: Usage of Electrocorticography (ECoG) is not clearly established. Robust evidence doesnot exist to support its regular usage in Long term Epilepsy associated tumors (LEATs) which constitutes approximately 25-35% cases of drug resistant epilepsy. METHODS: Prospective randomized controlled trial, including all patients operated for drug resistant epilepsy with non-eloquent area LEATs. Patients were randomized into 2 groups namely Group I (without usage of ECoG) and Group II (with ECoG usage). Group II patients further underwent tailored resections if necessary, as per ECoG practice protocols. Surgical outcomes were evaluated for seizure outcome (Engel scale) and adverse event profile. RESULTS: Total of 38 patients operated for LEATs having drug resistant epilepsy were included in the study with mean age of 21.1 years (range 2-46 years). 18 patients belonged to Group I and 20 patients belonged to Group II with mean follow-up period of 11.02 months (range 3-22 months). 30% patients (n = 6) in Group II underwent extended resection based on rhythmic persistent post resection spikes. 90% of Group II patients had Engel score Ia during follow up compared to 77.7% of Group I with Engel score Ia (p = 0.302). In Group II, 85.7% patients with extended tailored resection had Engel score Ia compared to 83.8% cases without extended resection (p = 0.904). CONCLUSIONS: Though ECoGs role may have been established in focal cortical dysplasia, its utility in LEATs is limited. Our randomized study confirmed that there is no added benefit conferred by the use of ECoG in LEATS. Additional tailored resections aided by ECoG also did not yield seizure outcome benefits in LEATS.